Educação infantil e racismo: um estado do conhecimento dos trabalhos de conclusão de curso das licenciaturas em pedagogia da UFSCar (2019-2025) - Santos, Mariana Aparecida dos (Universidade Federal de São Carlos, 2025)
This research investigates the presence and treatment of racial issues in Early Childhood Education within the academic productions of the Pedagogy program at the Federal University of São Carlos (UFSCar). The guiding questions are: Does the racial theme in Early Childhood Education appear in the works produced by graduates of the Pedagogy/UFSCar program? If so, what motivates these graduates to research the topic? The general objective is to map, discuss, and analyze the academic production of Undergraduate Theses (TCCs) from the Pedagogy/UFSCar program related to the treatment of Education for Ethnic-Racial Relations (ERER) between the first semester of 2019 and the first semester of 2025. The specific objectives are: (1) to understand the interests and justifications that underpin these works; and (2) to identify the predominant thematic approaches, considering categories such as pedagogical practice, teacher education, and racial belonging. The analyzed materials consist of Undergraduate Theses from the in-person Pedagogy program, from the Sorocaba and São Carlos campuses, available in the university’s Institutional Repository (RI). This is a mixed-methods study, based on the State of Knowledge methodology (Morosini, 2014; 2021), which seeks to identify and interpret the body of existing studies on a given topic within a defined time frame. Due to the scarcity of specific productions on the subject, an expanded inclusion criterion was adopted, encompassing not only works centered on Early Childhood Education but also those with potential application to that context, as they offer pedagogical and conceptual contributions to antiracist practices in daycare and preschool settings. The results reveal a dual institutional gap: the unequal rate of thesis deposit between campuses (29.4% in São Carlos and 85.4% in Sorocaba) and the marginalization of racial issues, resulting in 11 works (5.1%) analyzed in this research. It is concluded that, although limited, this production demonstrates a political and educational commitment to the construction of critical and antiracist pedagogical practices in teacher education.
Early childhood education and racism: a state of knowledge of undergraduate theses in pedagogy at UFSCar (2019-2025)
Keywords: Educação Infantil; Antirracismo; Trabalho de Conclusão de Curso; Pedagogia; UFSCar; Early Childhood Education; Antiracism; Final Course Project; Pedagogy; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade